Simulation of a ball on a beam model using a fuzzy-dynamic and a fuzzy-static sliding-mode controller - Magzoub, M.A. (Maxwell Science Publications, 2014)
This study presents the design of a Fuzzy Static (FS) and a Fuzzy Dynamic (FD) Sliding-Mode Controllers (SMC) for both basic and complete ball on beam system. At first, the FSSMC was designed for the simplified and the complete models. Then, the FDSMC was designed on the simplified and the comprehensive models of the system in which the ball is placed on a beam as well. In addition, the lyapunov stability and linearization were used to check the stability of the system. There is an in-built issue of chattering with (FSSMC). However, (FDSMC) counter it well. Also, FDSMC is effective with respect to matched disturbance rejection. It has been found out from this research study that the designs of the models which utilize a FDSMC with a comprehensive model of the system were more efficient than the designs that utilize the basic system's prototype. Lastly, a comprehensive comparative analysis is provided and MATLAB/SIMULINK outcomes confirm the dominance of FDSMC. Â© Maxwell Scientific Organization, 2014.